The God in Me: Faith, Reality TV, and Black Women - Egwu, Chetachi A. (Black Women's Portrayals on Reality Television: The New Sapphire, 2016)
The display of spirituality, faith and religion is not a new phenomenon among black women in the United States, nor is it new to the world of media. Africans came to the Americas with their own sense of spirituality and religion, and the awareness of a higher being became the mortar that bound the community together during the trials of enslavement and subsequent oppression. Not surprisingly, this legacy of worship continues to provide solace and strength, with black women at the helm.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice noir.e; 5-Autrice; 5-Créateur.rice PANDC; 5-Identités diasporiques; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

High Tea, Church Hats, Pastor Wives, and Friendships: A Critical Race Feminism Analysis of Black Women in Preachers of L.A. - Whittington Cooper, Elizabeth (Black Women's Portrayals on Reality Television: The New Sapphire, 2016)
The premise of the show revolves around six preachers in the Los Angeles area. They each pastor churches ranging from 3,500– 4,000 members; however, one pastor’s church has nearly 20,000 members (season 1: episode 1). A multitude of cameras follow the stories of each of the pastors’ lives, their relationships with each other, as well as their wives relationships with one another. The show has five black male preachers and one white male preacher. In season 1, all of the pastors— except for two— are married; one of the unmarried pastors is engaged to the mother of his child, and the other has a long-standing relationship with a female friend who frequently appears on the show. As viewers watch the show, they are given a glimpse into the world of evangelical preachers. Although at first glance the show seems to only focus on the men, the women provide an interesting glimpse at what it means to be a preacher’s wife, fiancée, or female companion. There were a total of eight episodes that aired over the course of two months. This chapter explores how black women and their friendships are portrayed on Preachers of L.A. — including the one white woman on the show. It also examines their discourse between one another— using critical race feminism to analyze the roles of these women as first ladies (a term used to describe the wives of pastors), their relationship with one other, and the conversations they have surrounding sex, marriage, relationships, and friendships. The chapter focuses on the first season of the show, which began in the fall of 2013. The show was later renewed for a second season, which began airing late summer 2014. This critique attempts to bring awareness to black women in the church and the discourse that perpetuates the stereotypes of black women on television. It also aims to initiate further conversations on various stereotypes— regardless of context— that have the potential to bear negatively on black women.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice noir.e; 5-Autrice; 5-Créateur.rice PANDC; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Making of Exile Culture: Iranian Television in Los Angeles - Naficy, Hamid (University of Minnesota Press, 1993)
Naficy explores the seemingly contradictory way in which immigrant media and cultural productions serve as the source both of resistance and opposition to the domination by host and home country's social values while simultaneously serving as vehicles for personal and cultural transformation and assimilation of those values.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice PANDC; Iran (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Introduction: I See Black People - Smith-Shomade, Beretta E. (Watching While Black, 2012)
This project has been engaging my thoughts for nearly a decade. I was forced to actually address it while sitting in our temporary home in Ile-Ife, Nigeria, watching world satellite TV with virtually no Blacks on it. In Nigeria, I became acquainted with Paris-based Fashion TV, U.S.-based Style Network, and the Australian production McLeod’s Daughters. Outside of M-Net’s Africa Magic, a network dedicated to showing Nollywood productions primarily, television was anything but Black. This whitening of the televisual frame, even in Black Africa, made me begin to consider the dearth of knowledge circulating about Black television programming, even when abundance
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice noir.e; 5-Créateur.rice PANDC; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Neoliberal Multiculturalism, Outsourced - Nadkarni, Asha (The Routledge Companion to Global Television, 2019)
This essay examines the 2010 NBC situation comedy Outsourced, with special attention to its representation of the racial politics surrounding business process outsourcing to India. Specifically, it discusses how Outsourced participates in what Jodi Melamed calls “neoliberal multiculturalism” to work through, symbolically and narratively, the realities and contradictions of globalized economies as they are experienced. By staging the dilemmas of outsourcing through the specter of the white male middle manager traveling to India to train Indian call center workers, Outsourced minimizes the affective labor necessarily performed by Indian call center workers and dramatizes outsourcing as a crisis of white U.S. masculinity alone. Moreover, it figures our white male protagonist as the global multicultural citizen to be emulated insofar as he models the appropriate attitude toward outsourcing and toward “other” cultures in general. Finally it suggests that the failure of the show has less to do with issues of cultural stereotyping and more to do with the failure of neoliberal multiculturalism to soothe anxieties around changing global economies.
Num Pages: 10
Keywords: 1-TV; 2-Approches sociologiques; 2-Méthodologie de recherche décoloniale; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice PANDC; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Making Queer Asiatic Worlds: Performance and Racial Interaction in North American Visual Novels - Patterson, Christopher B. (American Literature, 2022)
This paper argues that video games expose the presumptions separating “Asian America” and “Asia” in the traditional senses of isolation, origination, and presumed distance. It does so by focusing on the most “Asiatic” genre of video games today, the North American visual novel, which offers a counterdiscourse to normative modes of play and attempts to offer utopic spaces to reflect upon the “real” genres of race and neo–Cold War geopolitics. Using theories of performance from Dorinne Kondo and others, the author shows how queer indie visual novels are primarily aspirational, in that they build queer, utopic, and seemingly anti-racist worlds through the Asiatic space of the visual novel form. In so doing, they also allow players to explore the Asiatic as a means of repairing the traumas and distances of American imperial cultures. The article analyzes four visual novels to make this argument: three by non-racially-identifying North American designers—Doki Doki Literature Club! (2017) by Dan Salvato, Analogue: A Hate Story (2012) by Christine Love, and Heaven Will Be Mine (2018) by Aevee Bee—and Butterfly Soup (2017), a game by the queer Asian/American designer Brianna Lei. If games make the boundaries of Asia and America irrelevant, visual novels explore this irrelevance through Asiatic irreverence.
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice PANDC; _Nettoyé

The Iconography of Chicano Self-Determination: Race, Ethnicity, and Class - Goldman, Shifra M. (Art Journal, 1990)
In several cities in the Southwest and Midwest with sizable enclaves of Chicanos, there are to be found considerable numbers of images that have become leitmotifs of Chicano art. In their ubiquity, these motifs demonstrate that the Chicano phase of Mexican-American art (from 1965 to the 1980s) was nationally dispersed, shared certain common philosophies, and established a network that promoted a hitherto nonexistent cohesion. In other words, it was a movement, not just an individual assembly of Mexican-descent artists. In what follows, Chicano art is examined as statements of a conquered and oppressed people countering oppression and determining their own destiny, though not all the producers of these images necessarily saw their production in the political way they are framed below. Examples have been chosen specifically to show how, in response to exploitation, artists have taken an affirmative stance celebrating race, ethnicity, and class.
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice PANDC; _Nettoyé

Manuel Zapata Olivella, le muntu africain et la décolonisation des imaginaires et des épistémologies en Amérique Latine - Akassi, Clément Animan (Matraga - Revista do Programa de Pós-Graduação em Letras da UERJ, 2019)
Ce travail vise à montrer deux choses. La première, c’est de saisir toute l’importance du tournant postcolonial/afro-décolonial dans la construction d’une contre-épistémologie propre au sujet culturel colonisé africain. En d’autres termes, pour le sujet colonisé, cette contre-épistémologie sert à décoloniser les imaginaires, à partir d’un questionnement de la colonialité de l’épistémologie et du savoir donnés pour universels par l’occident. La deuxième chose, c’est que ̶ à quelques mois de la commémoration du centenaire de la naissance du prolixe et polygraphe auteur africain-colombien Manuel Zapata Olivella (1920-2004) ̶ cet article puisse le situer à sa juste place. Celle d’un sujet culturel colonisé africain des Amériques dont l’abondante production culturelle et la pensée, portées et révolutionnées par le concept de Muntu africain, participent de la décolonisation des imaginaires et de l’épistémologie
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Afrique (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Créateur.rice PANDC; 5-Créateur.rice noir.e; _Nettoyé

Unsettled Landscapes - Dees, Janet; Hofmann, Irene; Hopkins, Candice; Sanromán, Lucia (SITE Santa Fe, 2014)
Published by SITE Santa Fe on occasion of the inaugural SITElines Biennial, 'Unsettled Landscapes'. Unsettled Landscapes was curated by Janet Dees, Irene Hofmann, Candice Hopkins, and Lucía Sanromán. The exhibition, featuring 47 artists from 14 countries, looks at the urgencies, political conditions and historical narratives that inform the work of contemporary artists across the Americas–from Nunavut to Tierra del Fuego. Through three themes–landscape, territory, and trade–this exhibition expresses the interconnections among representations of the land, movement across the land, and economies and resources derived from the land."–Résumé de l'éditeur
Section: 223 pages : illustrations (principalement en couleur) ; 24 cm.
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 2-Étude des représentations; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique centrale (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice PANDC; 5-Créatrice; 5-Identités diasporiques; _Nettoyé

Interview with author, Dr. Laura Pérez - Ramirez, Abraham
Interview with author, Dr. Laura Pérez, Professor of Ethnic Studies at UC Berkeley on her most recent book, Eros Ideologies: Writings on Art, Sprituality, & the Decolonial.
Related with the book "Eros ideologies. Writings on art, spirituality, and the decolonial" of Laura Pérez
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Genre et sexualité; 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice LGBTQ+; 5-Créateur.rice PANDC; _Nettoyé

Eros ideologies. Writings on art, spirituality, and the decolonial. - Perez, Laura E (Duke University Press, 2019)
In 'Eros Ideologies' Laura E. Perez explores the decolonial through Western and non-Western thought concerning personal and social well-being. Drawing upon Jungian, people-of-color, and spiritual psychology alongside non-Western spiritual philosophies of the interdependence of all life-forms, she writes of the decolonial as an ongoing project rooted in love as an ideology to frame respectful coexistence of social and cultural diversity. In readings of art that includes self-portraits by Frida Kahlo, Ana Mendieta, and Yreina D. Cervantez, the drawings and paintings of Chilean American artist Liliana Wilson, and Favianna Rodriguez's screen-printed images, Perez identifies art as one of the most valuable laboratories for creating, imagining, and experiencing new forms of decolonial thought. Such art expresses what Perez calls eros ideologies: understandings of social and natural reality that foreground the centrality of respect and care of self and others as the basis for a more democratic and responsible present and future. Employing a range of writing styles and voices-from the poetic to the scholarly-Perez shows how art can point to more just and loving ways of being.
Related with the Podcast "Interview with author, Dr. Laura Pérez"
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Genre et sexualité; 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice LGBTQ+; 5-Créateur.rice PANDC; _Nettoyé

Only Skin Deep: Changing Visions of the American Self - Fusco, Coco; Wallis, Brian (Abrams and International Center of Photography, 2003)
"By bringing together a provocative selection of essays and images, Only Skin Deep: Changing Visions of the American Self addresses the issues of nation, race, and selfhood and how they are depicted in ways that are challenging and informative, prompting readers to consider the impact of photography on our everyday lives." "If photographs are chiefly responsible for perpetuating myths of American identity, can a different reading of these representations break down distorting stereotypes? This is the central question posed by Only Skin Deep. The authors in this book forcefully argue that race and nation - and, indeed, photography itself - are fictions, cultural constructions that shape our social interactions. Even as symbols, these photographic depictions of ethnic difference and cultural superiority have very real consequences. This collection of works and essays addresses, for example, the lingering consequences of American colonial expansion; the conflict between public and private visualizations of individuals; the role of commercial imagery in shaping gender roles; the impact of fantasy in ethnic or ethnographic photography; and the uses of science to provide justification for politicized depictions of "race."" "Accompanying a major exhibition of the same name, Only Skin Deep offers a critical rereading of the archive of the history of photography. This applies to the works of famous photographers - such as Dorothea Lange, Walker Evans, Ansel Adams, and Edward Steichen - as well as lesser-known historical figures, including Charles Eisenmann, Frances Benjamin Johnston, Will Soule, and Toyo Miyatake. A substantial part of the book is devoted to contemporary artists and photographers who have moved beyond the multicultural approach to representations of "race" and have made an investigation of the semiotics of cultural identity a prevalent theme over the past decade. Among the recent photographers included are: Nancy Burson, Nikki S. Lee, Glenn Ligon, Paul Pfeiffer, Hulleah Tsinhnahjinnie, Cindy Sherman, Lorna Simpson, and Andres Serrano."–(BOOK JACKET)
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice PANDC; 5-Créateur.rice noir.e; _Nettoyé

Game Devs & Others: Tales from the Margins - DePass, Tanya (CRC Press, 2018)
Game Devs & Others: Tales from the Margins tell the true stories of life in the industry by people of color, LGBTQIA and other marginalized identities. This collection of essays give people a chance to tell their stories and to let others know what life on the other side of the screen is like when you’re not part of the supposed “majority”. Key Features This book is perfect for anyone interested in getting into the games industry who feels they have a marginalized identity For those who wish to better diversify their studio or workplace who may or may not have access to individuals that could or would share their stories about the industry Includes initiatives aimed at diversifying the industry that have a positive or negative impact on the ongoing discussions Coverage of ajor news items about diversity, conferences aimed at or having diversity at its core of content and mission are discussed Included essays are written with as little game dev specific jargon as possible, makeing it accessible to people outside the industry as well as those in the scene but that may not have all the insider lingo
Google-Books-ID: Gv5cDwAAQBAJ
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Méthodologie de recherche décoloniale; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice LGBTQ+; 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; 5-Créateur.rice LGBTQ+; 5-Créateur.rice PANDC; 5-Créateur.rice autochtone; 5-Créateur.rice noir.e; 5-Créatrice; 5-Identités diasporiques; _Nettoyé

Featuring Females: Feminist Analyses of Media - Cole, Ellen; Daniel, Jessica Henderson (American Psychological Association, 2005)
"Featuring Females analyzes the portrayals of women in a variety of outlets, including reality television shows, films, print and electronic news programming, magazines, video games, and commercial advertising. A highly esteemed group of scholars and researchers provides informed, original psychological study, and their thought-provoking findings address the ways in which aging, race/ethnicity, body image, gender roles, sexual orientation and relationships, and violence are treated in the media. Featuring Females is a diverse volume, exploring images and characterizations of women young and old and inspiring discussion of the effects that these representations have on girls, women, and society at large"–
OCLC: 57754311
Keywords: 1-Jeux vidéo; 2-Analyses formalistes; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des industries culturelles; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; 5-Créateur.rice PANDC; 5-Créateur.rice noir.e; 5-Créatrice; _Nettoyé; _À analyser; _À vérifier-Cinéma; _À vérifier-Télé

Independent Videogames: Cultures, Networks, Techniques And Politics - Ruffino, Paolo (Routledge, 2021)
Independent Videogames investigates the social and cultural implications of contemporary forms of independent video game development. Through a series of case studies and theoretical investigations, it evaluates the significance of such a multi-faceted phenomenon within video game and digital cultures. A diverse team of scholars highlight the specificities of independence within the industry and the culture of digital gaming through case studies and theoretical questions. The chapters focus on labor, gender, distribution models and technologies of production to map the current state of research on independent game development. The authors also identify how the boundaries of independence are becoming opaque in the contemporary game industry – often at the cost of the claims of autonomy, freedom and emancipation that underlie the indie scene. The book ultimately imagines new and better narratives for a less exploitative and more inclusive videogame industry. Systematically mapping the current directions of a phenomenon that is becoming increasingly difficult to define and limit, this book will be a crucial resource for scholars and students of game studies, media history, media industries and independent gaming.
Keywords: 1-Jeux vidéo; 2-Analyses formalistes; 2-Approches sociologiques; 2-Genre et sexualité; 2-Humanités numériques; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Europe (corpus analysé); 4-Amérique centrale (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice LGBTQ+; 5-Auteur.rice PANDC; 5-Autrice; 5-Créateur.rice LGBTQ+; 5-Créateur.rice PANDC; _Nettoyé

Gaming Globally: Production, Play, and Place - Huntemann, Nina B.; Aslinger, Ben (Palgrave Macmillan, 2013)
Video games are inherently transnational by virtue of their industrial, textual, and player practices. This collection includes essays from scholars from eight countries analyzing game cultures on macro- and micro-levels and investigates the growing transnational nature of digital play
Section: xi, 279 p. : ill. ; 23 cm.
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Créateur.rice PANDC; 5-Créatrice; _Nettoyé